Tracking Trajectories using Sliding Control for Ball and Beam with deviated axis: Simulation and Experiment - Tran, Văn Thành; Do, Quốc Thịnh; Le, Trần Vũ Hoàng; Do, Hùng Anh; Dao, Đức Việt Anh; Ngo, Tiến Đại; Manh, Thế Lộc; Tran, Văn Tú (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Compared with linear algorithms, nonlinear algorithms ensure the system stability in terms of mathematics as well as better working space, especially in controlling the trajectories. In this paper, we build SMC controller with control parameters searched by GA for B&B with deviated axis – a classical SIMO. Thence, we also investigate this controller through experimental model by processor STM32F4. Through simulation and experiment, our trajectories tracking SMC controller is successful for this model.